Calcium aluminate cement conversion analysed by ptychographic nanotomography. (November 2020) - Shirani, S.; Cuesta, A.; De la Torre, A.G.; Diaz, A.; Trtik, P.; Holler, M.; Aranda, M.A.G.
Abstract: Calcium aluminate cements are used for special applications but are nowadays banned for general structural purposes due to the calcium aluminate hydrate conversion, that has led, for concretes fabricated with high water contents, to building collapses. The stoichiometries of these conversion chemical reactions are relatively well established but the consequences in porosity, key to predict durability, were unknown. Here, we have used hard X-ray ptychographic nanotomography to study the hydration of CaAl2 O4 at different temperatures and chiefly, at 4 °C and then at 50 °C to provoke conversion similar to field conditions. The mass densities of the resulting Al (OH)3 gels were 1.94, 1.98 and 2.23 g·cm −3, for samples hydrated at 4, 20 and 50 °C, respectively. These values are lower than that of gibbsite, 2.42 g·cm −3 . Above all, this 3D imaging technique has allowed measuring the secondary water porosity developed in the conversion, which has an average pore dimension close to 140 nm.